Fire, Flood and War from the East: Cultural Transfer in Altaic Modern Eschatology - Dmitrii Y. Doronin (Studia Litterarum)
The article examines modern Altai eschatology from the standpoint of cultural transfer. For this purpose, it gives an overview of sources of Altai eschatology, including the main versions (subtradition) of Altai eschatology as well as its oral and folklore genres. It shows that Altai eschatology, especially its Burkhanism version, has not only circular but also axial, linear, or “historical” sense of time. The problem of cultural transfer is revealed through a description of obvious Buddhist Central Asian influences and borrowings in the eschatology and, more broadly, in the mythology of the Altaians. In particular, the Buddhist doctrine of the kalpas is compared with the Altaic notions of eschatological elements of the aiguls. Borrowings from Mongolian and Buddhist eschatology and mythology receive detailed examination. The essay examines the specificity of Altaic eschatological ideas about the fiery disaster and the flood waters emerging at the end of time from under the earth. Finally, the essay explores folklore texts that demonstrate the mythologization of other states and peoples (primarily China and Russia) by Altaians in the folklore motifs of the eschatological war and foreign invasion. Mythological ideas about the last war between eschatological peoples are built on the messianic expectations of the coming Khan and on the memory of the historical upheavals of the past.